Schizotypal Traits are Associated with Poorer Executive Functioning in Healthy Adults - Louise, Stephanie; Gurvich, Caroline; Neill, Erica; Tan, Eric J.; Van Rheenen, Tamsyn E.; Rossell, Susan (Frontiers in Psychiatry, 2015)
Previous research has shown mild forms of the neurocognitive impairments seen in schizophrenia among healthy individuals exhibiting high schizotypal traits. This study aimed to explore associations between schizotypy and cognitive performance in an adult community sample. Ninety-five females and 79 males completed the Oxford-Liverpool Inventory of Feelings and Experiences (O-LIFE), which measures four separable aspects of schizotypy: cognitive disorganisation, unusual experiences, introvertive anhedonia and impulsive nonconformity. Subsequently, participants were administered a neurocognitive battery incorporating measures of executive skills including inhibition, cognitive flexibility, reasoning and problem solving along with measures of attention and processing speed and both verbal and spatial working memory. In line with predictions, the current study found that higher scores on the subscales of unusual experiences, cognitive disorganisation and impulsive non-conformity related to worse performance on a measure of inhibition. Additionally, as introvertive anhedonia increased, both attention and processing speed and reasoning and problem solving performance became more impaired. In conclusion, this study extends schizotypy literature by examining the subscales of the O-LIFE, and enables inferences to be drawn in relation to cognitive impairment in schizophrenia.